Combination-Combination Synchronization of Four Nonlinear Complex Chaotic Systems - Xiaobing Zhou; Lianglin Xiong; Xiaomei Cai (Abstract and Applied Analysis)
This paper investigates the combination-combination synchronization of four nonlinear complex chaotic systems. Based on the Lyapunov stability theory, corresponding controllers to achieve combination-combination synchronization among four different nonlinear complex chaotic systems are derived. The special cases, such as combination synchronization and projective synchronization, are studied as well. Numerical simulations are given to illustrate the theoretical analysis.